The Effects of Talent Management, Kaizen Programs, and Work Culture on Productivity at Pt Denso Manufacturing Indonesia (A Case Study of Employees in The Servo Motor Department) - Fifi Hanafiah; Suriyanti; Rizqon Hoeroni (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Human resources are a company’s most important asset, particularly a highly skilled workforce capable of adapting to the Fourth Industrial Revolution. The concept of the Fourth Industrial Revolution emphasizes the importance of a systematic approach to human resource management from recruitment and development to employee retention to achieve optimal productivity in the future. To this end, this study was conducted to analyze the influence of talent management, the Kaizen program, and work culture on employee productivity in the Servo Motor Department at PT Denso Manufacturing Indonesia. This is a quantitative study where the sample was selected using probability sampling, specifically random sampling. The population for this study consisted of 164 individuals, with a sample of 116 respondents. The results of this study indicate that through multiple linear regression analysis, it was found that talent management significantly increases employee productivity with a beta coefficient of 0.607 (p < 0.05). Work culture also contributes positively to productivity with a beta coefficient of 0.330 (p < 0.05). However, the Kaizen program did not show a significant effect on productivity (p = 0.065). Collectively, these three variables explain 80.5% of the variation in employee productivity (Adjusted R² = 0.805). This study recommends that PT Denso Manufacturing Indonesia strengthen the implementation of talent management and workplace culture to boost productivity, while improving the implementation of the Kaizen program to make it more effective.